Discussion on the Antipruritic Mechanism of Qiwei Antipruritic Based on Network Pharmacology and Molecular Docking Technology - Wang L; Deng T; Liu Y; Cheng H (Clinical, Cosmetic and Investigational Dermatology, 2023)
Luoxi Wang,1 Tinghan Deng,1 Ying Liu,1 Hongbin Cheng2 1Clinical Research on Skin Diseases School of Clinical Medicine, Chengdu University of TCM, Chengdu, People’s Republic of China; 2Dermatology of Department, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, People’s Republic of ChinaCorrespondence: Hongbin Cheng, Email chenghongbin@cdutcm.edu.cnObjective: To explore the mechanism of Qiwei antipruritic by using network pharmacology and molecular docking technology.Methods: The components and related targets of Qiwei antipruritic were screened by using the traditional Chinese medicine system pharmacology database (TCMSP and symmap databases). GeneCards and OMIM databases were used to screen itch-related targets. The protein–protein interaction (PPI) network between active ingredient targets and pruritus disease targets was constructed using STRING database. Cytoscape 3.8.0 software was used to draw the visualization network of “drug-component-target-signaling pathway” and screen the core targets. Gene ontology (GO) functional annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were performed using R software. AutoDock vina software was used to perform molecular docking of key targets and their corresponding key components.Results: There were 44 main components of Qiwei antipruritic compound, 118 corresponding targets and 3869 itch-related genes. A total of 82 predicted targets of Qiwei antipruritic in the treatment of pruritus were obtained. Eleven key targets were screened. Among the 23 KEGG enriched pathways, 12 signaling pathways were related to skin pruritus. Molecular docking results showed that the core components of Qiwei antipruritic, including quercetin, kaempferol, β-sitosterol, stigmasterol, luteolin, and preskimmianine, had good binding ability with ESR1, PPARG, IL6, TP53, and EGFR, and the docking scores were all less than − 4.Conclusion: The mechanism of Qiwei antipruritic may be related to histamine activation mechanism, calcium channel mechanism, inhibition of inflammatory signaling pathway, inhibition of neurotransmitters, and regulation of immune pathways. The traditional Chinese medicine compound Qiwei antipruritic can treat clinical pruritus through multiple targets and pathways.Keywords: Qiwei antipruritic, traditional Chinese medicine compound, network pharmacology, molecular docking, mechanism of action